General Foods Corporation radio script collection
Scripts for radio series sponsored by General Foods Corporation. Some scripts include annotations for sound effects or voice emphases; others contain commercials for sponsoring products. Programs represented include The Adventures of the Thin Man, The Adventures of Topper, and Portia Faces Life.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: General Foods Corporation; Adventures of the Thin Man (Radio program); Elocution; Radio advertising -- United States; Radio broadcasting -- Sound effects; Radio programs -- United States; Radio scripts; Adventures of Topper (Radio program); Portia Faces Life (Radio program)